STING agonist cGAMP enhances anti-tumor activity of CAR-NK cells against pancreatic cancer. (31st December 2022) - Da, Yanyan; Liu, Yuxia; Hu, Yuan; Liu, Wenzeng; Ma, Junpeng; Lu, Nan; Zhang, Chengsheng; Zhang, Cai
ABSTRACT: Activation of the stimulator of interferon gene (STING)-mediated innate immune response has been suggested as a promising therapeutic strategy for cancers. However, the effects of STING agonist on natural killer (NK) cell-mediated anti-tumor responses in pancreatic cancer remains unknown. Herein, we evaluated the effects of a classical STING agonist cyclic GMP-AMP (cGAMP) on NK cells in pancreatic cancer. We found that cGAMP could directly activate NK cells and enhance the sensitivity of pancreatic cancer cells to NK cell cytotoxicity, suggesting that cGAMP may become a potential adjuvant for NK cell therapy. In addition, combination of CAR-NK-92 cells targeting mesothelin and cGAMP displayed greater antitumor efficacy by inhibiting tumor growth and prolonging survival of the mouse model of pancreatic cancer. These results suggest that the combination of a STING agonist and NK cells may become a novel immunotherapy strategy for pancreatic cancer.